Die Pronominalsysteme der slavischen Sprachen - Kattein, Rudolf (Slavistische Beitraege, 1984)
This book was written on the occasion of a seminar "Linguistic categories - shown on Slavic material" at the University of Hamburg by discussing the fundamental semantic features found in natural languages.